2019
DOI: 10.1111/resp.13663
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for Enterobacteriaceae in patients hospitalized with community‐acquired pneumonia

Abstract: Backgroundand objective: Enterobacteriaceae (EB) spp. family is known to include potentially multidrug-resistant (MDR) microorganisms, and remains as an important cause of community-acquired pneumonia (CAP) associated with high mortality. The aim of this study was to determine the prevalence and specific risk factors associated with EB and MDR-EB in a cohort of hospitalized adults with CAP. Methods: We performed a multinational, point-prevalence study of adult patients hospitalized with CAP. MDR-EB was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 28 publications
0
41
0
1
Order By: Relevance
“…History of colonization or infection with a drug-resistant gram-negative bacillus in the previous 12 months, previous hospitalization with exposure to broadspectrum antibiotics, the presence of a tracheostomy, neutropenia, a history of pulmonary comorbidity (eg, cystic fibrosis, bronchiectasis, or recurrent exacerbations of COPD requiring glucocorticoid and antibiotic use) have been reported in the literature to increase the risk of resistant gram-negative bacilli. [37][38][39][40][41][42] Patients with any of these risk factors should be considered for initial empirical therapy against resistant gram-negative bacilli including P aeruginosa. b-Lactam antibiotics with activity against P aeruginosa, such as piperacillintazobactam or a carbapenem, should be used as core therapy.…”
Section: F Empirical Therapy: Specific Pathogensmentioning
confidence: 99%
“…History of colonization or infection with a drug-resistant gram-negative bacillus in the previous 12 months, previous hospitalization with exposure to broadspectrum antibiotics, the presence of a tracheostomy, neutropenia, a history of pulmonary comorbidity (eg, cystic fibrosis, bronchiectasis, or recurrent exacerbations of COPD requiring glucocorticoid and antibiotic use) have been reported in the literature to increase the risk of resistant gram-negative bacilli. [37][38][39][40][41][42] Patients with any of these risk factors should be considered for initial empirical therapy against resistant gram-negative bacilli including P aeruginosa. b-Lactam antibiotics with activity against P aeruginosa, such as piperacillintazobactam or a carbapenem, should be used as core therapy.…”
Section: F Empirical Therapy: Specific Pathogensmentioning
confidence: 99%
“…Approximately 6% of cases of CAP with etiological diagnosis are caused by multidrug-resistant (MDR) pathogens, the most frequently described being S. aureus and P. aeruginosa [19][20][21]. A recent multinational point prevalence study reported that the prevalence rates of drug-resistant S. pneumoniae and MDR Enterobacteriaceae in CAP were 1.3% and 1.2%, respectively [22,23]. MDR pathogens make the clinical management of CAP a real challenge for physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 21 eligible articles, nine were prospective studies [ 14 , 16 , 17 , 19 , 32 , 37 , 39 41 ] and twelve were retrospective studies [ 26 31 , 33 36 , 38 ]. Three articles [ 16 , 17 , 31 ] were conducted at multiple centers. Except for an international multicenter study [ 16 , 17 ], all other studies [ 14 , 15 , 19 , 26 41 ] were confined to one country.…”
Section: Resultsmentioning
confidence: 99%
“…We summarized the baseline characteristics of the included studies in Table 1 . The 21 eligible articles involved 7,650 patients and 1,360 MDR organisms, of which ten reported the risk factors for MDR GPB and GNB [ 15 , 19 , 26 , 28 , 31 , 33 , 34 , 38 , 39 , 41 ], ten for MDR GNB [ 14 , 16 , 17 , 27 , 29 , 30 , 32 , 35 , 36 , 40 ], and one for MDR GPB [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation